2024
DOI: 10.3390/ijms25021204
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell RNA Sequencing Reveals the Cellular Landscape of Longissimus Dorsi in a Newborn Suhuai Pig

Wei Xiao,
Nengjing Jiang,
Zhengyu Ji
et al.

Abstract: The introduction of single-cell RNA sequencing (scRNA-seq) technology has spurred additional advancements in analyzing the cellular composition of tissues. The longissimus dorsi (LD) in pigs serves as the primary skeletal muscle for studying meat quality in the pig industry. However, the single-cell profile of porcine LD is still in its infancy stage. In this study, we profiled the transcriptomes of 16,018 cells in the LD of a newborn Suhuai pig at single-cell resolution. Subsequently, we constructed a cellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Previously, intramuscular vascular stem cells (IVSC), composed of satellite cells, FAPs, immune cells, and endothelial cells, have been isolated from skeletal muscle of newborn piglets and used in adipogenesis studies. ,, However, the precise cellular origin of intramuscular fat cells remains unclear. Recently, single-cell RNA sequencing (scRNA-seq) has elucidated the diversity of cell population in tissues, providing insights into the heterogeneity of gene expression across cells. , Studies based on scRNA-seq have effectively revealed the molecular mechanisms underlying adipogenic formation in distinct regions of adipose tissue. Several studies have also documented the single-cell mapping of porcine skeletal muscle, , revealing the involvement of FAPs in intramuscular fat deposition. , However, FAPs exhibit heterogeneity, and as of now, the precise origin of IMF remains unclear. Moreover, there are few investigations focusing on the differences in the adipogenic mechanism of FAPs between fat-type and lean-type pigs.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, intramuscular vascular stem cells (IVSC), composed of satellite cells, FAPs, immune cells, and endothelial cells, have been isolated from skeletal muscle of newborn piglets and used in adipogenesis studies. ,, However, the precise cellular origin of intramuscular fat cells remains unclear. Recently, single-cell RNA sequencing (scRNA-seq) has elucidated the diversity of cell population in tissues, providing insights into the heterogeneity of gene expression across cells. , Studies based on scRNA-seq have effectively revealed the molecular mechanisms underlying adipogenic formation in distinct regions of adipose tissue. Several studies have also documented the single-cell mapping of porcine skeletal muscle, , revealing the involvement of FAPs in intramuscular fat deposition. , However, FAPs exhibit heterogeneity, and as of now, the precise origin of IMF remains unclear. Moreover, there are few investigations focusing on the differences in the adipogenic mechanism of FAPs between fat-type and lean-type pigs.…”
Section: Introductionmentioning
confidence: 99%